2015
DOI: 10.1117/1.jbo.20.2.026003
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of diabetic foot complications with infrared thermography by asymmetric analysis

Abstract: Early identification of diabetic foot complications and their precursors is essential in preventing their devastating consequences, such as foot infection and amputation. Frequent, automatic risk assessment by an intelligent telemedicine system might be feasible and cost effective. Infrared thermography is a promising modality for such a system. The temperature differences between corresponding areas on contralateral feet are the clinically significant parameters. This asymmetric analysis is hindered by (1) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 21 publications
0
93
0
4
Order By: Relevance
“…Liu et al demonstrated a sensitivity of 85% and a specificity of 98.4% for computer‐based automated detection of foot complications (e.g. callus, blisters, redness or ulceration) using asymmetric analysis of thermal images in combination with color imaging . Surprisingly, a large cohort study of 362 patients with a foot ulcer and a concomitant infection showed no significant change in left‐to‐right foot temperature difference …”
Section: Resultsmentioning
confidence: 99%
“…Liu et al demonstrated a sensitivity of 85% and a specificity of 98.4% for computer‐based automated detection of foot complications (e.g. callus, blisters, redness or ulceration) using asymmetric analysis of thermal images in combination with color imaging . Surprisingly, a large cohort study of 362 patients with a foot ulcer and a concomitant infection showed no significant change in left‐to‐right foot temperature difference …”
Section: Resultsmentioning
confidence: 99%
“…The measurement of foot temperature changes in time is used in many areas of medicine. It is indispensable in the widely understood diagnosis of: perfusion of diabetic foot – the changes in mean temperatures of some selected areas of the foot during administration of drugs (insulin and others) are of interest; hyperhidrosis – in assessing the impact of the patient's emotional state and other factors on perspiration; Raynaud's disease – in assessing the impact of treatment, and primarily the performed physiotherapy procedures, on feet cooling/warming; atherosclerosis – in assessing the degree of pathology and the impact of reliever medication on changes in blood supply and thereby temperature; foot mycosis (interdigital tinea) – in assessing the progress of treatment. …”
Section: Results and Discussionmentioning
confidence: 99%
“…perfusion of diabetic foot – the changes in mean temperatures of some selected areas of the foot during administration of drugs (insulin and others) are of interest;…”
Section: Results and Discussionmentioning
confidence: 99%
“…thermal imaging [120], and multispectral imaging [40], to automatically detect diabetic foot complications and to differentiate among these complications.…”
Section: Resultsmentioning
confidence: 99%
“…Details about this have been addressed in [120]. In this way, the PSI reconstruction would be focused on the foot area only to avoid the influence of the background.…”
Section: Calibration and Image Pre-processingmentioning
confidence: 99%